Comparison of Barrett TK Universal II and Barrett Universal II TCRP Formulas in Power Calculations for 3 Presbyopia-Correcting Intraocular Lenses - Li Q; Liu X; Yang J; Dai Y; Li W (Clinical Ophthalmology, 2024)
Qingchen Li,1– 3 Xinyi Liu,1,2 Jiasong Yang,1,2,4 Yumeng Dai,1,2 Wensheng Li1,2,4 1Shanghai Aier Eye Hospital, Aier Eye Hospital Group Co. Ltd, Shanghai, 201103, People’s Republic of China; 2Shanghai Aier Eye Institute, Shanghai, 201103, People’s Republic of China; 3Department of Ophthalmology, the Second Xiangya Hospital of Central South University, Changsha, Hunan Province, 410011, People’s Republic of China; 4Aier School of Ophthalmology, Central South University, Changsha, Hunan Province, 410015, People’s Republic of ChinaCorrespondence: Wensheng Li, Shanghai Aier Eye Hospital, Aier Eye Hospital Group Co. Ltd, No. 83 Wuzhong Road, Xuhui District, Shanghai, 201103, People’s Republic of China, Email drlws@qq.comPurpose: To compare Barrett TK Universal II and Barrett Universal II TCRP calculations in the power calculations for 3 presbyopia-correcting intraocular lenses (PC-IOL).Methods: This observational study involved 64 eyes from 64 patients who prepared to undergo extraction of crystalline lenses combined with PC-IOL (Symfony ZXR00, PanOptix TFNT00, or AT LISA tri 839MP) implantation. All eyes underwent ocular biometric measurements with IOLMaster 700 and Pentacam HR, and the interdevice agreement of measurements including total keratometry (TK, IOLMaster 700) and total corneal refractive power (TCRP, Pentacam HR) was evaluated. IOL power calculations were performed using TK-based Barrett TK Universal II and TCRP-based Barrett Universal II calculations, respectively.Results: Paired t-tests showed that the differences in white-to-white diameter, central corneal thickness, anterior chamber depth, and mean TK between IOLMaster 700 and Pentacam HR were slight but significant (all P< 0.05), and the differences in recommended IOL power for emmetropia between two Barrett calculations were also significant in 3 PC-IOLs (all P< 0.05). The ROC curve showed that the AUC was 0.917 (95% CI, 0.820– 0.971) for the absolute value of the difference between TK and TCRP in discriminating the difference of ≥ ± 0.5 D in predicted IOL power with best cutoff values of 0.4 D.Conclusion: The novel Barrett TK Universal II formula built in IOLMaster 700 is comparable to TCRP-based Barrett Universal II calculation for IOL power calculation of PC-IOLs, and the convenience of using the Barrett TK Universal II formula should be founded on measurement consistency between devices.Keywords: presbyopic corrections, intraocular lens power calculation, refractive prediction accuracy, swept-source optical biometer, scheimpflug tomography